Sucrose Metabolism in Plastids - Gerrits, Nathalie (American Society of Plant Physiologists, 2001)
The question whether sucrose (Suc) is present inside plastids has been long debated. Low Suc levels were reported to be present inside isolated chloroplasts, but these were argued to be artifacts of the isolation procedures used. We have introduced Suc-metabolizing enzymes in plastids and our experiments suggest substantial Suc entry into plastids. The enzyme levansucrase from Bacillus subtilis efficiently synthesizes fructan from Suc. Targeting of this enzyme to the plastids of tobacco (Nicotiana tabacum) and potato (Solanum tuberosum) plants leads to high-level fructan accumulation in chloroplasts and amyloplasts, respectively. Moreover, introduction of this enzyme in amyloplasts leads to an altered starch structure. Expression of the yeast invertase in potato tuber amyloplasts results in an 80% reduction of total Suc content, showing efficient hydrolysis of Suc by the plastidic invertase. These observations suggest that Suc can enter plastids efficiently and they raise questions as to its function and metabolism in this organelle.